Gwet Kappa Trust Factor-Based Repeated Node Taxonomy Scheme for Malicious Adversaries Detection - Saravanan, R; Ilavarasan, E (International Journal of Computer Sciences and Engineering, 2025)
There is a growing interest for mobile ad hoc network (MANET) in the recent years for many time-critical applications, such as military applications or during a disaster recovery scenario in a collaborative manner. In this paper, we proposed a Gwet Kappa Trust Factor-Based Repeated Node Taxonomy Scheme (GKRNTS) for malicious adversaries node detection which focuses on the discrimination of mobile nodes into malicious and benevolent nodes. The interactions between the mobile nodes are periodically monitored and the elucidated data are useful for determining the degree of collaboration between the mobile nodes through the computation of Gwet Kappa. The Gwet Kappa parameter used in this Repeated Node Taxonomy Scheme is stored with each node as an adjacency matrix that stores the interaction activity between the nodes of the network. This adjacency matrix quantifies the extent of cooperation existing between the mobile nodes of the network and they are considered as the taxonomy of the mobile nodes during data communication. The proposed GKRNTS is compared against the TPFPPDM and NPDRDS techniques by simulation using NS2 network simulator has led to promising results in terms of reduced packet rate, energy consumption and computational cost